Implementation of Modified Problem Based Learning (PBL) in Improving Learning Outcomes of Physics Vocational School for Optical Materials - Ika Vidiasari Aristawati; Wiyanto Wiyanto; Budi Astuti (Postgraduate, University of Mataram, 2021)
The purpose of research on the implementation of Problem Based Learning (PBL) can improve students' physics learning outcomes in terms of knowledge and skills. Classroom Action Research was conducted in two cycles, the subject of the research was class X APHP 03 with 35 students. The data collection method used was a test for knowledge and skill aspects through observation. Qualitative descriptive data analysis method for the knowledge aspect by percentage of students' mastery level classically and the skill aspect through the observation sheet scoring. Learning outcomes from cycle I and cycle II have increased in the knowledge aspect by 17.14%. Aspects of student skills increase in the indicators of systematic presentation, mastery of the material and pronunciation at the time of presentation, so that the implementation of Problem Based Learning can improve student learning outcomes